Participação popular e os valores notícia no telejornalismo: interação e cidadania - Moraes, Adriana Teixeira de (2012)
This work constitutes a reflection on citizenship in the media, specifically television. It is based on the principle that the participation of the viewer in the content of television news should set up as a right and hence the guarantee of citizenship. The paper explains how journalists can interfere with the practice of citizenship from the criteria of newsworthiness that shape daily life for these professionals in the production process of news published in TV journalism. The object of the research is the section "I want to see on TV" produced by TV Anhanguera which was created to be a channel of interactivity between viewers and journalists.